2011
DOI: 10.2298/vsp1108661s
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of nosocomial colonization/infection caused by Acinetobacter spp. in patients of six surgical clinics in war and peacetime

Abstract: This study provides additional important information about the risk factors of nosocomial Acinetobacter spp. infections in a large cohort of surgical patients. This is also the first study that directly examines epidemiological differences between NCI caused by Acinetobacter spp. during the war and peace period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…There is a study which provides important information about the RFs of nosocomial Acinetobacter spp. infections in a large cohort of surgical patients in MMA 25 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a study which provides important information about the RFs of nosocomial Acinetobacter spp. infections in a large cohort of surgical patients in MMA 25 .…”
Section: Discussionmentioning
confidence: 99%
“…First, we excluded duplicate cases that were defined in other studies [4, 5], and this exclusion may have caused a distortion in the bacteremia results. Second, it was a retrospective study which was conducted after the patients' data such as the isolated microorganisms from blood cultures were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…In the case the same causative microorganism was isolated from a patient more than once, the initial isolated microorganism was included in the analysis, and when different types of microorganisms were isolated, each microorganism was included in the analysis. The above definitions of duplicated cases were based on other published studies [4, 5]. The date of the microorganism culture in reference to the date of the burn was analyzed and results isolated after day 60 of the burn were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…40,69,70 Although mechanical ventilation leads to improved oxygen exchange in the lungs, there are certain risks that predispose to the presence of HAI, such as prolonged intubation, reintubation, enteral feeding, aspiration, use of paralytic agents, extremes of age, severity of underlying pathophysiology, prior surgery, and prior antibiotic use. [89][90][91][92] ICU admission 56,58 and days of ICU hospitalization 55,57 were other RFs for HAI. Other studies have also associated increased risk with the ICU, an environment that favors the natural selection of microorganisms because of the clinical severity of patients and the invasive procedures.…”
Section: Extrinsic Rfs For Infectionmentioning
confidence: 99%
“…In the cohort studies, the observed extrinsic RFs were central venous catheter (CVC) placement, 23,25,[50][51][52][53] ICU admission, [54][55][56][57][58] duration of surgery, 13,17,20,24 steroid use, 13,15,59 previous antibiotic use, 55,60 exposure to cephalosporins before the first episode of infection, 58,61 number of administered antibiotics, 53,62 antimicrobial therapy within 90 days, 63 reoperation, 20,64 transfusion, 50,56,64 invasive mechanical ventilation (IMV), 50,52,65 hospitalization time, 66,67 and a high score on the Acute Physiology and Chronic Health Disease Classification System II. 14,55 Other less frequent extrinsic RFs were found ( Supplementary Table S1).…”
Section: Extrinsic Rfs For Infectionmentioning
confidence: 99%